Factors Influencing the Business Performance of Scaleups. A Comparative Analysis. - Slávik, Štefan; Ivana Mišúnová Hudáková; Mišún, Juraj; Bednár, Richard (European Journal of Sustainable Development, 2025)
The analysis of the literature on scaleups has shown that the conditions and factors that influence the existence and favorable development of scaleups are known, but most studies take a declarative stance on the topic and provide mostly indirect evidence without a direct relationship to business performance. There is therefore a research gap that can be filled by a better and more detailed understanding of the factors that influence the business performance of scaleups. The purpose of the research is to identify the causes and reasons that positively or negatively affect the business performance of scaleups. A field study of 92 scaleups was conducted. The source of knowledge about the studied scaleups is personal experience recorded in a questionnaire. Research without intermediaries is more authentic and allows for immediate feedback. The research sample was divided into more and less powerful scaleups. Using comparative analysis, the causes and reasons for different business performance were identified. The performance difference between more and less powerful scaleups is a consequence of (a) more efficient conversion of a business idea into a useful product, (b) internationalization of business, (c) a larger and broader offer of various types of cooperation with external partners, (d) more valuable enterprise resources of all kinds, (e) better fulfilment of explicitly set and relevant goals, (f) greater implementation capacities, (g) doing business on international markets and (h) more effective promotion and advertising. The results of empirical research and comparative analysis in the range of identified parameters bring new knowledge about the causes of higher performance of scaleups and at the same time provide guidance on how to achieve such higher performance. Keywords: scaleup, business performance, comparative analysis, performance factors, high-performance scaleups, low-performance scaleups